2017
DOI: 10.14814/phy2.13482
|View full text |Cite
|
Sign up to set email alerts
|

Effect of renal denervation on urine angiotensinogen excretion in prenatally programmed rats

Abstract: Prenatal programming results in an increase in blood pressure in adult offspring. We have shown that compared to control adult offspring whose mothers were fed a 20% protein diet, programmed adults whose mothers were fed a 6% protein diet during the last half of pregnancy have an increase in renal sympathetic nerve activity and urinary angiotensinogen/creatinine levels. We hypothesized that the increase in urinary angiotensinogen was mediated by renal sympathetic nerve activity in programmed rats. In this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…In a search towards a better understanding of the pathophysiological mechanisms behind the BP-lowering effect by RDN, we attempted to search for potential differences in RAAS hormones and endogenous catecholamines as induced by RDN. While our findings are in line with several preclinical studies, 10,11 previous animal data by Zhao et al suggested that RDN might suppress an increase in plasma aldosterone in 28 dogs with progressive heart failure at 3 weeks. 15 In addition, Hong et al demonstrated a clear suppression in aldosterone release following RDN in rats with angiotensin (Ang)-II-induced hypertension after 14–17 days.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In a search towards a better understanding of the pathophysiological mechanisms behind the BP-lowering effect by RDN, we attempted to search for potential differences in RAAS hormones and endogenous catecholamines as induced by RDN. While our findings are in line with several preclinical studies, 10,11 previous animal data by Zhao et al suggested that RDN might suppress an increase in plasma aldosterone in 28 dogs with progressive heart failure at 3 weeks. 15 In addition, Hong et al demonstrated a clear suppression in aldosterone release following RDN in rats with angiotensin (Ang)-II-induced hypertension after 14–17 days.…”
Section: Discussionsupporting
confidence: 93%
“…9 Conversely, the effects of RDN on the RAAS has only been studied in a limited number of preclinical studies, failing to demonstrate a correlation between BP reduction and change in sodium excretion or in RAAS activity. 10,11 To date, dedicated studies focusing on the link between RDN and neurohormones in vivo are lacking. Therefore, in the present study, we aimed to assess the effect of RDN on RAAS hormones and endogenous catecholamines as an attempt to understand the BP-lowering effect.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that hyperinnervation of the renal nerves may potentially be contributing to the elevation in blood pressure and kidney disease in SFK and has implications for children with SFK. A role for renal sympathetic overactivity in promoting hypertension is also evident in other models of reduced kidney mass, such as the developmental programming models (maternal glucocorticoid exposure) and genetic models (SHR) (Gattone et al, 1990;Alexander et al, 2005;Dagan et al, 2008;Kett and Denton, 2011;Mansuri et al, 2017). Prenatal exposure to dexamethasone is well known to cause a reduction in nephron number and elevation in blood pressure in studies in various species (Singh et al, 2012).…”
Section: Renal Denervationmentioning
confidence: 99%
“…Prior animal studies provided support for the theory that RDN would decrease BP preferentially when the RAAS is activated [10–12,16]; contrasting negative studies have also been reported [17,18]. Human studies measuring the hormonal effects of RDN are mixed; they follow an early report by Buhler demonstrating the antihypertensive effect of propranolol in 47 hypertensive patients correlated closely with both baseline levels of renin activity and with the degree of renin suppression produced, pointing to an associated neurogenic mechanism of action [19].…”
Section: Discussionmentioning
confidence: 99%